Emotional and Spiritual Intelligence (ESQ) of Children in Islamic Education in The Family Environment - Faridh, Tri Ahmad (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2018)
In Islam, the term family is known as usrah or ahl, which is a basic and natural institution, in which every human being must experience. Families have reproductive, religious, recreational, educational, and social functions. By carrying out the functions and roles mentioned above, it is expected that children are intellectually intelligent, emotionally and spiritually intelligent. But so far intelligence, known by the general public especially in the family environment, is only intellectual intelligence or IQ, where the level of child achievement is measured only through the Intelligence Quotient (IQ) test alone. However, there are still other intelligence potentials such as Emotional Quotient (EQ) and or Spiritual Quotient (SQ) which can develop in children. One combinative and innovative intelligence development offered by Ary Ginanjar Agustian is by combining EQ and SQ without denying IQ. It is a combination of brain ability and emotional enthusiasm with the values of justice and divine norms which make spiritual as a means of transfer of knowledge and transfer of value with the name ESQ concept.